Integrin-mediated signaling induced by simian virus 40 leads to transient uncoupling of cortical actin and the plasma membrane. - Lilli Stergiou; Manuel Bauer; Waltraud Mair; Damaris Bausch-Fluck; Nir Drayman; Bernd Wollscheid; Ariella Oppenheim; Lucas Pelkmans (PLoS ONE)
Simian Virus 40 (SV40) is a paradigm pathogen with multivalent binding sites for the sphingolipid GM1, via which it induces its endocytosis for infection. Here we report that SV40 also utilizes cell surface integrins to activate signaling networks required for infection, even in the absence of the previously implicated glycosphingolipids. We identify ILK, PDK1, the RhoGAP GRAF1 and RhoA as core nodes of the signaling network activated upon SV40 engagement of integrins. We show that integrin-mediated signaling through host SV40 engagement induces the de-phosphorylation of Ezrin leading to uncoupling of the plasma membrane and cortical actin. Our results provide functional evidence for a mechanism by which SV40 activates signal transduction in human epithelial cells via integrins in the context of clathrin-independent endocytosis.